2004
DOI: 10.1001/archsurg.139.8.870
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Mapping and Sentinel Lymphadenectomy for Primary and Metastatic Pulmonary Malignant Neoplasms

Abstract: Background: Mediastinal lymph node sampling understages a significant number of lung cancers, even when nodes are evaluated by immunohistochemical techniques. Intraoperative lymphatic mapping and sentinel lymphadenectomy allows focused pathologic evaluation of a few lymph nodes that accurately stage the entire basin. Hypothesis: Lymphatic mapping and sentinel lymphadenectomy is a practical and accurate method of staging lymph nodes that drain primary and metastatic neoplasms of the lung. Design and Setting: Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 30 publications
4
17
0
1
Order By: Relevance
“…From the viewpoint of sentinel lymph node mapping, the results of recently launched clinical trials support the anatomical concept. While the percentage of skip metastasis in lung cancer patients with N2 disease has been reported to be around 20-40% [1][2][3][4][5][6][7], sentinel node mapping in non-small cell lung cancer patients in various stages revealed a similar percentage of mediastinal (N2) sentinel nodes of 16.7-31% with a high sensitivity rate of more than 90% [16][17][18]. Arguably, the direct drainage system appears the most plausible main channel of skip mediastinal nodal spread of cancer cells.…”
Section: Discussionmentioning
confidence: 94%
“…From the viewpoint of sentinel lymph node mapping, the results of recently launched clinical trials support the anatomical concept. While the percentage of skip metastasis in lung cancer patients with N2 disease has been reported to be around 20-40% [1][2][3][4][5][6][7], sentinel node mapping in non-small cell lung cancer patients in various stages revealed a similar percentage of mediastinal (N2) sentinel nodes of 16.7-31% with a high sensitivity rate of more than 90% [16][17][18]. Arguably, the direct drainage system appears the most plausible main channel of skip mediastinal nodal spread of cancer cells.…”
Section: Discussionmentioning
confidence: 94%
“…Soltesz et al (2005) suggested that the use of blue dye could not adequately identify the sentinel node in thoracic malignancies because of poor tissue penetration and the presence of anthracosis. Faries et al (2004) stated that blue dye was generally visible within subpleural lymphatic channels but might fade rapidly from anthracotic pulmonary lymph nodes ex vivo. Little et al (1999) adopted the position that anthracosis in intrathoracic lymph nodes caused a problem in identifying the blue node.…”
Section: Discussionmentioning
confidence: 99%
“…The mediastinal and interlobar surfaces were chosen because of the limited time of research during the autopsy and the greater probability of vessel visualization, which had been confirmed by prior tests. The used method was consistent with an intraoperative lymphatic mapping and sentinel lymphadenectomy, in which after injecting blue dye, the visceral pleura was closely observed to identify the blue-stained lymphatic channels leading to sentinel nodes (Faries et al, 2004). Sentinel nodes were examined by routine hematoxylin-eosin staining (Faries et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Its role is also being explored for other superficial cancers that spread preferentially by lymphatics such as melanoma [2], squamous cell carcinoma of the head and neck [3] and vulva [4]. The technique is also applicable to the staging of intracavitatory neoplasms such as lung [5] and colon [6] and in the correct clinical setting may be more accurate than any radiological staging technique including FDG-PET [7].…”
Section: Mmentioning
confidence: 99%